2016
DOI: 10.1016/j.biocontrol.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget effects of orchard pesticides on natural enemies: Lessons from the field and laboratory

Abstract: The nontarget effects of insecticide programs used to control codling moth, Cydia pomonella Linnaeus (Lepidoptera: Tortricidae), were studied in large-plot field trials in apples, pears, and walnuts in the western United States. We assessed the health of the natural enemy community by sampling the abundance of natural enemies and by monitoring for outbreaks of secondary pests. The insecticides used in the field tests overlapped those tested in laboratory bioassays. Using these parallel lab and field studies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 29 publications
(24 reference statements)
1
35
0
Order By: Relevance
“…Given growers' preference for pesticide modification and the increasing availability of reduced risk pesticides with different impacts on natural enemies, we believe growers might be especially interested in the entomological findings from our USDA-SCRI project designed to enhance BC in western U.S. orchard systems. Especially notable are the results from laboratory and field research focused on the effects of reduced risk pesticides on natural enemies and strategies for selecting and timing pesticide sprays to protect natural enemies Beers et al, 2016;Jones et al, 2016;Mills et al, 2016;Shearer et al, 2016).…”
Section: Selective Adoption Of Biological Control Practices Biologicamentioning
confidence: 99%
“…Given growers' preference for pesticide modification and the increasing availability of reduced risk pesticides with different impacts on natural enemies, we believe growers might be especially interested in the entomological findings from our USDA-SCRI project designed to enhance BC in western U.S. orchard systems. Especially notable are the results from laboratory and field research focused on the effects of reduced risk pesticides on natural enemies and strategies for selecting and timing pesticide sprays to protect natural enemies Beers et al, 2016;Jones et al, 2016;Mills et al, 2016;Shearer et al, 2016).…”
Section: Selective Adoption Of Biological Control Practices Biologicamentioning
confidence: 99%
“…However, insecticides were not so likely to explain variability in the natural enemies of those pests, suggesting that the products used by these growers were preferentially affecting the pests and not the beneficial natural enemies. These results provide some reassurance that using selective insecticides such as buprofezin, CpGV and tebufenozide or methoxyfenozide, which have few effects on nontarget insects (Rumpf et al ., ; Shaw et al ., ; Lo, ; Shaw and Wallis, ; Rogers et al ., ; Beers et al ., ), can preserve biological control services, as intended in integrated pest management systems. The involvement of fertilizers, in conjunction with insecticides, in the best models to explain pests caught on sticky traps suggests that further research to examine the influence of fertilizers on the effectiveness of insecticides against apple pests could yield useful information for optimizing pest control practices.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence to indicate that some fungicides and plant growth regulators may have toxic effects on some invertebrates (Hassan et al ., ; Adamski & Ziemnicki, ; Dagli & Bahsi, ; Sutherland et al ., ; Martinou et al ., ). Relationships between the toxicity ratings and volumes of pesticides applied and invertebrate populations have been demonstrated in vineyards (Thomson and Hoffmann, ), kiwifruit orchards (Todd et al ., ) and apple orchards (Beers et al ., ). Studies examining the influence of fertilizers on insect herbivores have generally shown a positive response to nitrogen (especially among sucking insects) but varying responses to phosphorus and potassium (Awmack & Leather, ; Fagan et al ., ; Myers & Gratton, ; Butler et al ., ; Rashid et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, there are five papers in this issue that address different aspects of pesticide effects on natural enemy populations in both laboratory and field settings Beers et al, 2016a;Beers et al, 2016b;Mills et al, 2016a;Shearer et al, 2016). These papers show that, in general, laboratory bioassays based on life table response experiments and the use of a demographic approach to evaluation of the combined lethal and sub-lethal effects of pesticides on natural enemies provided an effective way to estimate the potential for disruption of natural enemy populations .…”
Section: Pesticide Effects On Natural Enemiesmentioning
confidence: 99%
“…Unfortunately, the use of large-plots with suitable controls proved to be logistically difficult, expensive, and required a degree of serendipity with respect to whether there was a sufficient abundance of both secondary pests and their natural enemies at the selected field sites to differentiate treatment effects. Despite the challenges and difficulties associated with the field trials, our project represents one of the largest field and laboratory studies to test the effects of some of the reduced-risk insecticides and fungicides on a range of predators and parasitoids found in tree crops in the western U.S. Beers et al, 2016b;Shearer et al, 2016).…”
Section: Pesticide Effects On Natural Enemiesmentioning
confidence: 99%